Ford Foundation annual report. - Ford Foundation; Ford Foundation; Ford Foundation ([New York Ford Foundation], 2001)
The president's report to the trustees and statement of grants.
Title varies slightly: 1954 called The Ford Foundation report.
Report year for 1954 ends Sept. 30; 1955- covers period Oct. to Sept. 30.
Keywords: Foundations -- United States -- Periodicals; Research Support -- United States -- Periodicals; Training Support -- United States -- Periodicals